Localisation Loss in the French Versions of Websites from the Andalusian Agri-Food Sector - Ramírez-Delgado, Cristina de las Montañas (Íkala, Revista de Lenguaje y Cultura, 2024)
Research in translation studies addressing the corporate website text genre has reported some content loss that occurs in localized versions when compared to the original versions. This study focuses on the contrastive analysis of a corpus of homepages and products sections from corporate websites from the Andalusian agri-food sector, studying their original versions (in Spanish) and the versions localised into English and French, according to a localization error taxonomy. The analysis focuses on assessing content loss in French versions, given that France is one of the main export destinations of the Andalusian agri-food industry. It is worth noticing that English versions tend to have less shortcomings than those localised into other languages, which may due to the international status of this language. Results show mainly shortcomings related to content omissions, untranslated text, and English text in versions localised into French, which puts French versions at a disadvantage in relation to English versions.